Recrutar. Produzir. Abastecer: repensar a produção e o comércio agrícolas em tempo de guerras (1369-1400) - Leandro Ribeiro Ferreira (Medievalista)
The aim of this paper is to study the agricultural production and its trade in the context of Portuguese wars between 1369 and 1400. This narrative will present the scars of the war in Medieval Portugal, while I seek to rethink some Portuguese historiograpic topics related with agricultural production and its trade in these times, namely price speculation, agrarian crisis and famines, concluding with an analysis to the Lei das Sesmarias promulgation, in 1375, by Dom Fernando.